Predictive Efficacy of Ultrasound Doppler Parameters in the Diagnosis of Intrauterine Growth Restriction and Associated Perinatal Outcomes in a Tertiary Care Setting - Khatoon, Sitara; Modi, Bhoomi; Shukla, Ashish Kumar; Sharma, Ashok Kumar; Ali, Asif (Journal of Neonatal Surgery, 2025)
Introduction: Intrauterine growth restriction (IUGR) remains a significant contributor to perinatal morbidity and mortality. Early and accurate diagnosis using Doppler ultrasonography is crucial for optimizing outcomes. This study aimed to evaluate the predictive efficacy of various Doppler parameters in diagnosing IUGR and determining perinatal outcomes in high-risk pregnancies. Methods: A prospective observational study was conducted at a tertiary care hospital over six months, including 60 high-risk pregnant women between 28-40 weeks gestation. Comprehensive Doppler assessment of umbilical artery (UA), middle cerebral artery (MCA), uterine arteries (UTA), and calculation of cerebroplacental (CP) ratio was performed. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of various Doppler indices were calculated for predicting adverse perinatal outcomes. Results: Hypertensive disorders of pregnancy constituted 76.7% of cases, with abnormal UA PI observed in 61.7% and abnormal CP ratio in 58.3% of subjects. Adverse perinatal outcomes occurred in 65% of cases, with higher rates in hypertensive disorders (70.6-78.9%) compared to GDM (33.3%). UA PI demonstrated the highest sensitivity (83.05%) for predicting adverse outcomes, while MCA PI showed the highest specificity (90.32%). CP ratio and UA PI exhibited the best overall diagnostic accuracy (81.11%) among all parameters. NICU admission (53.3%) and low birth weight (40%) were the most common adverse neonatal outcomes. Conclusion: Umbilical artery PI and cerebroplacental ratio emerged as the most accurate predictors of adverse perinatal outcomes in high-risk pregnancies. Implementation of a standardized protocol for Doppler assessment with emphasis on these parameters can significantly improve risk stratification and guide appropriate timing of delivery, ultimately enhancing perinatal outcomes.